Institutions and bilateral trade in Africa: an application of Poisson's estimation with high-dimensional fixed effects to structural gravity model - Alhassan, Abdulkareem; Payaslioglu, Cem (Routledge Journals, Taylor & Francis Ltd, 2020)
This study provides a comparative analysis of the effect of political and economic institutions on bilateral trade of emerging and low-income African countries. Using the structural gravity model estimated by the Poisson pseudo-maximum likelihood with high-dimensional fixed effects (PPMLHDFE) estimator, the study reveals that both political and economic institutions are fundamental determinants of bilateral trade in Africa. However, the effect differs by type and components of the institutions and levels of income of the countries. Generally, the findings show that institutions have greater impact on trade of the emerging African economies (EE) than the low-income countries (LICs). Relatively, economic institutions affect trade more than political institutions in the LICs, while the reverse is the case for EE. Hence, the design of an institutional framework that aimed at facilitating bilateral trade should consider the peculiarities of the countries in terms of their level of income and the various facets of institutions.
Keywords: Institutions; bilateral trade; structural gravity model; Poisson estimation; Africa